Perbandingan Metode Kuadrat Terkecil dan Metode Rata-rata Bergerak dalam Peramalan Jumlah Pengunjung Wisata Panorama Geosite Hutaginjang Sumatera Utara - Simaremare, Yehezekyel; Tarigan, Enita Dewi Br. (Pattimura Proceeding, 2024)
The methods used in this research are the Least Square method and the Moving Average method. The use of this method is intended to compare which method is the most accurate and has the smallest forecasting error using the Mean Absolute Percentage Error (MAPE) method. The data used in this research is data on the number of visitors to the Panorama Geosite Hutaginjang tourist attraction from December 2021 to May 2024. The results of research and data analysis found that the MAPE values ​​for the Least Square method, Moving Average period 3 (MA(3)) and Moving Average period 5 (MA(5)) are 16.627% , 21.691% and 19.703%. From the MAPE values ​​obtained, it can be determined that the most accurate method is the Least Square method.